Answer

Verified

450.3k+ views

Hint: First of all factorise the denominator of the given expression that is \[12{{x}^{2}}-11x-15\] in its linear factors. Then write the numerator that is 46 + 13x in terms of these linear factors of the denominator.

Here, we have to resolve the following expression into partial fractions.

Let us consider the given expression as

\[D=\dfrac{46+13x}{12{{x}^{2}}-11x-15}\]

Let us consider, \[A=46+13x\]

And \[B=12{{x}^{2}}-11x-15\]

Therefore, \[D=\dfrac{A}{B}....\left( i \right)\]

First of all, we will factorize B.

In B, we can write \[11x=20x-9x\]

Therefore, we get

\[B=12{{x}^{2}}-\left( 20x-9x \right)-15\]

\[\Rightarrow B=12{{x}^{2}}-20x+9x-15\]

Or, \[B=\left( 12{{x}^{2}}-20x \right)+\left( 9x-15 \right)\]

By taking 4x common from \[\left( 12{{x}^{2}}-20x \right)\] and 3 common from \[\left( 9x-15 \right)\], we get

\[\Rightarrow B=4x\left( 3x-5 \right)+3\left( 3x-5 \right)\]

By taking \[\left( 3x-5 \right)\] common, we get,

\[B=\left( 3x-5 \right).\left( 4x+3 \right)\]

By putting the values of A and B in equation (i), we get

\[D=\dfrac{A}{B}=\dfrac{46+13x}{\left( 3x-5 \right).\left( 4x+3 \right)}\]

Now, to resolve D into partial fractions, let us consider,

\[D=\dfrac{P}{\left( 3x-5 \right)}+\dfrac{Q}{\left( 4x+3 \right)}.....\left( ii \right)\]

Or, \[D=\dfrac{46+13x}{\left( 3x-5 \right).\left( 4x+3 \right)}=\dfrac{P}{\left( 3x-5 \right)}+\dfrac{Q}{\left( 4x+3 \right)}\]

Now, we will solve for P and Q to find the partial fractions.

By simplifying RHS, we get

\[\dfrac{46+13x}{\left( 3x-5 \right).\left( 4x+3 \right)}=\dfrac{P\left( 4x+3 \right)+Q\left( 3x-5 \right)}{\left( 3x-5 \right)\left( 4x+3 \right)}\]

By cancelling the like terms from both sides, we get

\[46+13x=P\left( 4x+3 \right)+Q\left( 3x-5 \right)\]

By simplifying the above equation, we get

\[46+13x=4Px+3P+3Qx-5Q\]

We can write it as,

\[46+13x=\left( 4P+3Q \right)x+\left( 3P-5Q \right)\]

By equating the coefficient of x and constant terms from LHS and RHS, we get

\[4P+3Q=13....\left( iii \right)\]

And, \[3P-5Q=46....\left( iv \right)\]

Now, we will multiply equation (iii) by 3 and equation (iv) by 4.

We get,

\[12P+9Q=39....\left( v \right)\]

\[12P-20Q=184....\left( vi \right)\]

By subtracting equation (v) from equation (vi), we get,

\[\left( 12P-20Q \right)-\left( 12P+9Q \right)=184-39\]

\[\Rightarrow -20Q-9Q=145\]

\[\Rightarrow -29Q=145\]

Or, \[Q=\dfrac{145}{-29}\]

Therefore, we get

\[Q=-5\]

By putting the values of Q in equation (iii),

We get,

\[4P+3\left( -5 \right)=13\]

\[\Rightarrow 4P-15=13\]

\[\Rightarrow 4P=13+15\]

\[\Rightarrow 4P=28\]

\[\Rightarrow P=\dfrac{28}{4}\]

Therefore, we get P = 7.

By putting the values of P and Q in equation (ii). We get,

\[D=\dfrac{7}{\left( 3x-5 \right)}+\dfrac{\left( -5 \right)}{\left( 4x+3 \right)}\]

Therefore, \[\dfrac{46+13x}{12{{x}^{2}}-11x-15}=\dfrac{7}{\left( 3x-5 \right)}-\dfrac{5}{\left( 4x+3 \right)}\] has been resolved into partial fraction.

Note: Whenever the degree of denominator is greater than numerator, always first try to factorize the denominator in these types of questions. Then solve for A and B by solving

\[\dfrac{mx+n}{\left( x-a \right)\left( x-b \right)}=\dfrac{A}{\left( x-a \right)}+\dfrac{B}{\left( x-b \right)}\]

like in the above solution. Finally, students should always cross check if the partial fractions are giving the same expression as given in the question by solving it.

Here, we have to resolve the following expression into partial fractions.

Let us consider the given expression as

\[D=\dfrac{46+13x}{12{{x}^{2}}-11x-15}\]

Let us consider, \[A=46+13x\]

And \[B=12{{x}^{2}}-11x-15\]

Therefore, \[D=\dfrac{A}{B}....\left( i \right)\]

First of all, we will factorize B.

In B, we can write \[11x=20x-9x\]

Therefore, we get

\[B=12{{x}^{2}}-\left( 20x-9x \right)-15\]

\[\Rightarrow B=12{{x}^{2}}-20x+9x-15\]

Or, \[B=\left( 12{{x}^{2}}-20x \right)+\left( 9x-15 \right)\]

By taking 4x common from \[\left( 12{{x}^{2}}-20x \right)\] and 3 common from \[\left( 9x-15 \right)\], we get

\[\Rightarrow B=4x\left( 3x-5 \right)+3\left( 3x-5 \right)\]

By taking \[\left( 3x-5 \right)\] common, we get,

\[B=\left( 3x-5 \right).\left( 4x+3 \right)\]

By putting the values of A and B in equation (i), we get

\[D=\dfrac{A}{B}=\dfrac{46+13x}{\left( 3x-5 \right).\left( 4x+3 \right)}\]

Now, to resolve D into partial fractions, let us consider,

\[D=\dfrac{P}{\left( 3x-5 \right)}+\dfrac{Q}{\left( 4x+3 \right)}.....\left( ii \right)\]

Or, \[D=\dfrac{46+13x}{\left( 3x-5 \right).\left( 4x+3 \right)}=\dfrac{P}{\left( 3x-5 \right)}+\dfrac{Q}{\left( 4x+3 \right)}\]

Now, we will solve for P and Q to find the partial fractions.

By simplifying RHS, we get

\[\dfrac{46+13x}{\left( 3x-5 \right).\left( 4x+3 \right)}=\dfrac{P\left( 4x+3 \right)+Q\left( 3x-5 \right)}{\left( 3x-5 \right)\left( 4x+3 \right)}\]

By cancelling the like terms from both sides, we get

\[46+13x=P\left( 4x+3 \right)+Q\left( 3x-5 \right)\]

By simplifying the above equation, we get

\[46+13x=4Px+3P+3Qx-5Q\]

We can write it as,

\[46+13x=\left( 4P+3Q \right)x+\left( 3P-5Q \right)\]

By equating the coefficient of x and constant terms from LHS and RHS, we get

\[4P+3Q=13....\left( iii \right)\]

And, \[3P-5Q=46....\left( iv \right)\]

Now, we will multiply equation (iii) by 3 and equation (iv) by 4.

We get,

\[12P+9Q=39....\left( v \right)\]

\[12P-20Q=184....\left( vi \right)\]

By subtracting equation (v) from equation (vi), we get,

\[\left( 12P-20Q \right)-\left( 12P+9Q \right)=184-39\]

\[\Rightarrow -20Q-9Q=145\]

\[\Rightarrow -29Q=145\]

Or, \[Q=\dfrac{145}{-29}\]

Therefore, we get

\[Q=-5\]

By putting the values of Q in equation (iii),

We get,

\[4P+3\left( -5 \right)=13\]

\[\Rightarrow 4P-15=13\]

\[\Rightarrow 4P=13+15\]

\[\Rightarrow 4P=28\]

\[\Rightarrow P=\dfrac{28}{4}\]

Therefore, we get P = 7.

By putting the values of P and Q in equation (ii). We get,

\[D=\dfrac{7}{\left( 3x-5 \right)}+\dfrac{\left( -5 \right)}{\left( 4x+3 \right)}\]

Therefore, \[\dfrac{46+13x}{12{{x}^{2}}-11x-15}=\dfrac{7}{\left( 3x-5 \right)}-\dfrac{5}{\left( 4x+3 \right)}\] has been resolved into partial fraction.

Note: Whenever the degree of denominator is greater than numerator, always first try to factorize the denominator in these types of questions. Then solve for A and B by solving

\[\dfrac{mx+n}{\left( x-a \right)\left( x-b \right)}=\dfrac{A}{\left( x-a \right)}+\dfrac{B}{\left( x-b \right)}\]

like in the above solution. Finally, students should always cross check if the partial fractions are giving the same expression as given in the question by solving it.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

The 3 + 3 times 3 3 + 3 What is the right answer and class 8 maths CBSE

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

How many crores make 10 million class 7 maths CBSE

Difference Between Plant Cell and Animal Cell

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE

Write a letter to the principal requesting him to grant class 10 english CBSE